Controllable synthesis of hollow periodic mesoporous organosilica spheres with radial mesochannels and their degradable behavior. Issue 26 (13th June 2018) - Sun, Yangyi; Chen, Min; Wu, Limin
Abstract : Hollow periodic mesoporous organosilica spheres with radial mesochannels have been efficiently and controllably synthesized only through introducing a pre-hydrolysis process. Abstract : Hollow periodic mesoporous organosilica spheres (HPMOSs) have some important special applications owing to their unique properties, but current syntheses usually involve various template methods that are time-consuming. Herein, we report a highly efficient and controllable synthesis of HPMOSs with radial mesochannels, only through introducing a pre-hydrolysis process to the commercially available bissilylated organosilanes (R′O)3 Si–R–Si(OR′)3 with CTAB. The HPMOSs are robust with a mean diameter as small as 45 nm and a shell thickness as thin as 14 nm. A cytotoxicity assay indicates that the obtained HPMOSs possess good biocompatibility, and the HPMOSs with thioether groups are degradable under a 10 mM glutathione microenvironment. The amphiphilic organosilica precursors derived from the pre-hydrolysis process, CTAB micelles, and ethanol contribute to the formation of the HPMOSs.